FEATURES OF THE IMPLEMENTATION OF COMPULSORY HEALTH INSURANCE IN THE REPUBLIC OF UZBEKISTAN (European Journal of Interdisciplinary Research and Development, 2025)
The introduction of compulsory health insurance (CHI) in the Republic of Uzbekistan is one of the key areas of ongoing reforms in the national healthcare system. The purpose of introducing compulsory medical insurance is to create a sustainable financial mechanism that ensures equal access of the population to quality medical services, optimizes costs and increases the efficiency of resource allocation in the healthcare sector. In recent years, Uzbekistan has been actively modernizing its healthcare infrastructure, implementing public-private partnerships, and strengthening the role of digital technologies, making the transition to an insurance-based model particularly relevant. The article analyzes the regulatory framework for the development of compulsory medical insurance, studies international experience (Germany, South Korea, Kazakhstan) and assesses the prospects for adapting these models to the conditions of Uzbekistan. Particular attention is paid to the benefits of introducing compulsory medical insurance, such as improving the quality of services, creating a competitive environment among medical institutions, and increasing the transparency of financial flows. Potential risks and challenges are also considered, including the need for digital transformation, workforce training, and improving financial literacy among the population. The obtained results demonstrate that the successful implementation of compulsory medical insurance in Uzbekistan requires a phased implementation, strengthening of the institutional framework, active participation of the private sector, and the creation of an effective system for monitoring and evaluating the quality of medical care. The presented analysis can be used as a scientific and practical basis for further improvement of the compulsory medical insurance reform and increasing the sustainability of the national healthcare system.